Penggunaan Aplikasi Mobile Mindfulness GFR Bermanfaat untuk Mengelola Stres Mahasiswa di Akademi Keperawatan YKY Yogyakarta - Nunung Rachmawati (Poltekkes Kemenkes Kendari, 2020)
The student is one of the academic stress-prone classes. Academic stress may be brought on by busy classes, overcrowded classes, laboratory examinations, and written examinations. Using technology can help students individually handle stress. The use of an android program named